Diet Soft Drink Consumption is Associated with an Increased Risk of Vascular Events in the Northern Manhattan Study - Gardener, Hannah (Springer-Verlag, 2012)
BACKGROUND: Diet and regular soft drinks have been associated with diabetes and the metabolic syndrome, and regular soft drinks with coronary heart disease. OBJECTIVE: To determine the association between soft drinks and combined vascular events, including stroke. DESIGN: A population-based cohort study of stroke incidence and risk factors. PARTICANTS: Participants (N = 2564, 36% men, mean age 69 ± 10, 20% white, 23% black, 53% Hispanic) were from the Northern Manhattan Study. MAIN MEASURES: We assessed diet and regular soft drink consumption using a food frequency questionnaire at baseline, and categorized: none (<1/month, N = 1948 diet, N = 1333 regular), light (1/month-6/week, N = 453 diet, N = 995 regular), daily (≥1/day, N = 163 diet, N = 338 regular). Over a mean follow-up of 10 years, we examined the association between soft drink consumption and 591 incident vascular events (stroke, myocardial infarction, vascular death) using Cox models. KEY RESULTS: Controlling for age, sex, race/ethnicity, education, smoking, physical activity, alcohol consumption, BMI, daily calories, consumption of protein, carbohydrates, total fat, saturated fat, and sodium, those who drank diet soft drinks daily (vs. none) had an increased risk of vascular events, and this persisted after controlling further for the metabolic syndrome, peripheral vascular disease, diabetes, cardiac disease, hypertension, and hypercholesterolemia (HR = 1.43, 95% CI = 1.06–1.94). There was no increased risk of vascular events associated with regular soft drinks or light diet soft drink consumption. CONCLUSIONS: Daily diet soft drink consumption was associated with several vascular risk factors and with an increased risk for vascular events. Further research is needed before any conclusions can be made regarding the potential health consequences of diet soft drink consumption. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11606-011-1968-2) contains supplementary material, which is available to authorized users.